Proses dan Hasil Penerjemahan Mahasiswa (Studi Kasus Pada Mahasiswa Translation Theory and Practice Di STAIN Pamekasan) - Mosleh Habibullah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
Research focus consists of: What method students use in process translating text from native language (BSu) to target language (BSa) and what process of mistake occasionally occurs in translating observed from the result of text translation BSu to BSa. This research employs qualitative approach by descriptive analysis paradigm. This data collecting procedure includes documentation, interview, and observation. Data validity by: data analysis through systematic arrangement and trace, interview transcript, field note, conclusion and verification, triangulation method. The result of research found: 1. Method which collage students use in translating process is placed in two categories, those are translation method pressed on BSu (NL): word by word translation, literal translation, faithful translation, and semantic translation, BSa (TL): press on: adaptation, free translation, idiomatic translation, and communicative translation. 2. Translation technique in this alternative step answers problem formulated on research problem, concerning translation procedure of religion text which is done by college students Translation Practice Semester VI from English to Indonesian, namely borrowing, loan translation (claque), literal translation, transposition, modulation, equivalence, and adaptation. 3 language mistake analyses in translation presented in this paper is study which analyze one paragraph from text 1 until text 4 above. Furthermore, comprehending about definition of translation error is language error. Language error can happen in every linguistic level because language produced by word, sentence and meaning, error which needs to analyze covered phonology, morphology, syntactic and semantic.Based on the result, it can be concluded that translating process done by college students is good wholly. Technique 1: using literal translation method. Technique 2: free translation method. Technique 3: adaptation method. Technique 4: unacceptable by the reader, from translation technique in the research is found from the text which college students translate, error in table 1, there are 3 errors, in table 2 there are six language errors, in table 3 there are six errors. In table 4 there are seven errors.However, researcher finds inadequacy which is caused by mastering vocabulary, phrase, idiom, and students’ inadequacy in using grammatical Principal from BSu (NL). Besides that, it is possible that time allocation is not enough, 100 minutes in 2 sks translation theory and 100 minutes in 2 sks translation practice